You are on page 1of 14

# Fourier and Laplace Transforms and Their

Applications

Feng
c Liu, 2007
Department of Mechanical and Aerospace Engineering
University of California, Irvine, CA 92697-3975

## 1.1 Fourier Series in Terms of sin ωn t and cos ωn t

Let fT (t) be a function over [−T, T ] that satisfies the following Dirichlet conditions

## 1. fT (t) is continuous except a finite number of discontinuities of first kind;

2. there are only a finite number of extrema.

## Then fT (t) can be expanded in terms of the following Fourier Series:

a0 X
fT (t) = + (an cos ωn t + bn sin ωn t) (1)
2 n=1

where
π
ωn = n (2)
T
is the angular frequency of the n-th harmonic and
π
∆ω = (3)
T
is the base angular frequency. The Fourier coefficients are given by the following integrals.
1 T
Z
an = fT (t) cos ωn tdt (4)
T −T
1 T
Z
bn = fT (t) sin ωn tdt (5)
T −T
n = 0, 1, 2, . . .

1
Equation (1) may be written as

X
fT (t) = A0 + |An | cos ( ωn t − φn ) (6)
|{z} |{z} |{z} |{z}
mean value n=1 amplitude frequency phase

where
a0
A0 = (7)
2
p
|An | = a2n + b2n (8)
bn
φn = tan−1 (9)
an
If we write An as a complex number

## An = |An | eiφn (10)

it will then contain both the amplitude and phase information of the Fourier component of
f (t) of the angular frequency ωn . We have constructed a one-to-one mapping between a
function f (t) in the ‘time’ domain and a discrete function (an infinite sequence) in the
‘Frequency’ domain, i.e., {(ωn , An ) : n = 0, 1, 2, . . .}. The Fourier-series theorem
guarrantees that the two are equivalent (except at points of discontinuity). In other words,
we can represent a time-domain function (periodic with a finite period) in terms of its
(discrete) frequency spectrum.

Notice in the above we may replace the time variable t by the spatial variable x to
study a spatial function. In that case, we can then replace the angular frequency ω by the
wave number κ and the half period T by the half wave length λ.

## 1.2 Fourier Series in terms of eiωn t

The Fourier series in the form of Eqn. (1) may be regarded as an expansion of f (t) in terms
of the orthogonal basis vectors {1, cos ω1 t, sin ω1 t, cos ω2 t, sin ω2 t, . . .}. These basis vectors
may be converted to the complex-valued basis vectors eωn t by using the Euler identities:

eiωn t + e−iωn t
cos ωn t = (11)
2

eiωn t − e−iωn t
sin ωn t = (12)
2i

2
Substituting them into Eq. (1), we get

a0 X eiωn t + e−iωn t eiωn t − e−iωn t
fT (t) = + [an + bn ]
2 n=1
2 2i

a0 X an − ibn iωn t an + ibn −iωn t
= + [ e + e ]
2 n=1
2 2

X
= F0 + (Fn eiωn t + F−n e−iωn t )
n=1

where
Z T
a0 1
F0 = = fT (t)dt
2 2T −T
Z T
an − ibn 1
Fn = = fT (t)e−iωn t dt
2 2T −T
Z T
an + ibn 1
F−n = = fT (t)eiωn t dt
2 2T −T
The above equations may be combined to yeild two simple equations as the alternative
Fourier Series expansion formulas for fT (t).

X
fT (t) = Fn eiωn t (13)
n=−∞

## where the new coefficient is defined as

Z T
1
Fn = fT (t)e−iωn t dt (14)
2T −T

Equations (13) and (14) may be interpreted and remembered easily by regarding the
summation as an expansion of fT (t) in terms of the complex-valued basis vectors
φ = {. . . e−iωn t , e−iωn−1 t , . . . , e−iω1 t , e0t , eiω1 t , eiω2 t , . . . , eiωn t , . . .}. The inner product of two
complex-valued functions is defined as
Z T
< f (t), g(t) >≡ f (t)g(t)dt (15)
−T

It can be easily shown that the new basis vectors are orthorgonal and k φn k2 = 2T , ie.,
Z T 
iωm t ωn t i(ωm −ωn )t 2T m = n
<e , e >= e dt = (16)
−T 0 m 6= n

The coefficients for the series expansion of Eqn. (13) are then

## < fT (x), eiωn t >

Fn =
k eiωn t k2

3
which readily reduces to Eqn. (14).

Unlike the real-valued Fourier series expansion defined by Eqns. (1-5), Equations (13)
and (14) work also for complex-valued functions fT (t). The coefficients Fn are in general
complex numbers, which can be written as

## Fn = |Fn |eiφn (17)

Like An , |Fn | and φn contain the amplitude and phase information, respectively, of the
frequency ωn , except now each frequency component is split into a positive and a negative
part. For a real function fT (t): F−n = F¯n .

## 1.3 Fourier Transform

The above expansion is performed for a function fT (t) defined over [−T, T ]. The expansion
is also valid outside the interval [−T, T ] provided fT (t) is extended beyond [−T, T ] as a
periodic function with the period 2T . For a non-periodic function f (t) in the infinite
domain −∞ < t < +∞, we can take a window [−T, T ] and view f (t) within this window as
fT (t). We can then expand fT (t) in terms of its Fourier series within [−T, T ] and consider
the limit as T → ∞, i.e.,
+∞  Z T 
X 1 −iωn τ
f (t) = lim fT (t) = lim fT (τ )e dτ eiωn t
T →∞ T →∞
n=−∞
2T −T
+∞
∆ω T
X  Z 
−iωn τ
= lim fT (τ )e dτ eiωn t
T →∞
n=−∞
2π −T

If we define a function of ω Z T
FT (ω) = fT (t)e−iωt dt (18)
−T

and let ω take the uniformly distributed values ωn = n∆ω along the ω axis as n runs from
−∞ to ∞, we may then write the Fourier series expansion as

1 X
f (t) = lim FT (ωn )eiωn t ∆ω
2π T →∞ n=−∞

Notice that as T → ∞, ∆ω = Tπ → 0, and the summation in the above equation yields the
original definition of the Riemann integral of FT (ω)eiωt in ω. Thus, we have the exact
integral Z ∞
1
f (t) = F (ω)eiωt dω (19)
2π −∞
where from Eqn. (18) the function F (ω) is
Z ∞
F (ω) = f (t)e−iωt dt (20)
−∞

4
We define it as the Fourier transform of the function f (t) in the time domain and denote it
as Z ∞
F (ω) = F{f (t)} ≡ f (t)e−iωt dt (21)
−∞

For the function F (ω) in the Frequency domain, we define the inverse Fourier transform
Z ∞
−1 1
F {F (ω)} ≡ F (ω)eiωt dω (22)
2π −∞
Eqn. (19) states that f (t) is equal to the inverse transform of F (w). However, Eqn. (19) is
only derived by formally taking T to ∞. A rigorous proof of the convergence of the Fourier
integrals is needed but skipped here. Insteady, we simply state the following
Fourier Integral Theorem:
If f (t) satisfies in (−∞, ∞)

## 1. Dirichlet condition for any finite interval,

R∞
2. −∞ | f (t) | dt < +∞ (absolute integrable),

## then, the following Fourier transform exists

Z ∞
F{f (t)} ≡ F (ω) = f (t)e−iωt dt (23)
−∞

and ∞
f (t + 0) + f (t − 0)
Z
−1 1
F {F (ω)} ≡ F (ω)eiωt dω = (24)
2π −∞ 2

## Let α, β be two constants in R or C, f1 (t) and f2 (t) be two functions and

F1 (ω) = F{f1 (t)} and F2 (ω) = F{f2 (t)}. We have

1. Linearity
The Fourier transform operator F and its inverse F −1 are both linear, i.e.,
F{αf1 (t) + βf2 (t)} = αF{F1 (t)} + βF{F2 (t)} (25)
and
F −1 {αF1 (ω) + βF2 (ω)} = αF −1 {F1 (ω)} + βF −1 {F2 (ω)} (26)

2. Translation Property

## F{f (t ± t0 )} = e±iωt0 F{f (t)}

F −1 {F (ω ∓ ω0 )} = f (t)e±iω0 t

5
3. Differentiation
0
F{f (t)} = iωF{f (t)}
00
F{f (t)} = (iω)2 F{f (t)} = −ω 2 F{f (t)}
F{f (n) (t)} = (iω)n F{f (t)}

## Proof: integration by parts and use the fact

Z ∞
0
lim f (t) = 0 (from |f (t)|dt < +∞)
t→±∞ −∞

4. Integration
Z t
1
F{ f (t)dt} = F{f (t)}
−∞ iω
(27)

5. Product
Z ∞ Z ∞
1
f1 (t)f2 (t)dt = F1 (ω)F2 (ω)dω
−∞ 2π −∞

6. Energy integral
Let F(ω) = F {f (t)}, then Parseval Equality:
Z ∞ Z ∞
2 1
|f (t)| dt = |F (ω)|2 dω
−∞ 2π
Z−∞

1
= S(ω)dω
2π −∞
(28)

where
S(ω) = |F (ω)|2
is called the energy spectrum/energy density function of f (t).

7. Convolution
The convolution of f1 (t) and f2 (t) is defined as
Z ∞
f1 (t) ∗ f2 (t) ≡ f1 (t)f2 (t − τ )dτ (29)
−∞

Then,
F{f1 (t) ∗ f2 (t)} = F1 (ω)F2 (ω) (30)
Similarly, we have
1
F{f1 (t)f2 (t)} = F1 (ω) ∗ F2 (ω) (31)

6
2 Application of Fourier Transform to PDE

## 2.1 First-Order Wave Equation

∂u ∂u
+c = 0, −∞ < x < +∞, t > 0
∂t ∂x

u(x, 0) = f (x)

## U (ω, t) = F{u(x, t)}.

Performing the Fourier transform on both the PDE and the initial condition, we reduce the
PDE into an ODE
dU
− iωcU = 0
dt
U (ω, 0) = F{f (x)} = F (ω)
Solution of the ODE gives

## Using the translation theorem, we obtain the inverse transform of U (ω, t)

u(x, t) = f (x − ct)

## 2.2 Second-order Wave Equation

∂2u 2

 ∂t2
= c2 ∂∂xu2 −∞ < x < +∞, t > 0
u(x, 0) = f (x)
ut (x, 0) = g(x)

Again, by performing the Fourier transform in x, we reduce the PDE problem into an ODE
problem. Let

## U (ω, t) = F{u(x, t)}

F (ω) = F{f (x)}
G(ω) = G{g(x)}

then, we have
d2 v

 = −c2 ω 2 U
dt2
U (ω, 0) = F (ω)
Ut (ω, 0) = G(ω)

7
General solution to the ODE is

## U (ω, t) = Φ(ω)e−iωct + Ψ(ω)eiωct

where φ(x) and ψ(ω) are two arbitrary functions of ω. Performing the inverse
transformation and making use of the translation theorem, we get the general solution
traveling-wave solution
u(x, t) = φ(x − ct) + ψ(x + ct)
from which we may proceed as before to obtain the D’lambert solution by applying the
initial conditions. Alternatively, we may determined the form of Φ(ω) and φ(ω) by using
the initial conditions on the frequency domain before performing the inverse transforms.
We then have
1 1
Φ(ω) = 1/2[F (ω) − G(ω)]
iω c
1 1
Ψ(ω) = 1/2[F (ω) + G(ω)]
iω c
By using the integration property, we find the inverse transforms of Φ(ω) and Ψ(ω)

1 x
Z
φ(x) = 1/2[f (x) + g(ξ)dξ]
c −∞
1 x
Z
ψ(x) = 1/2[f (x) − g(ξ)dξ]
c −∞

Application of the translation property then yeilds directly the D’Lambert solution

1 x+ct
Z
u(x, t) = 1/2[f (x − ct) + f (x + ct)] + g(ξ)dξ
2c x−ct

## u(x, 0) = f (x) − ∞ < x < +∞ (33)

Performing Fourier Transform in x for the PDE (32) and the initial condition, we obtain

dU
= ν(iω)2 U = −ω 2 αU
dt
where
U (ω, t) = F{u(x, t)}
U (ω, 0) = F {u(x, 0)} = F {f (x)} = F (ω)

8
Treating ω as a parametes, we obtain the solution to the above ODE problem
2 νt 2 νt
U (ω, t) = U (ω, 0)e−ω = F (ω)e−ω
Application of the convolution theorem yields
2
u(x, t) = f (x) ∗ F −1 {e−ω νt }
 
1 −x2
= f (x) ∗ √ e 4νt
4πνt
Z ∞
1 (x−ξ)2
= √ f (ξ)e− 4νt dξ
4πνt −∞
Suppose
f (x) = δ(x − x0 )
then
Z ∞
1 (x−ξ)2
G(x, x0 , t) = √ δ(ξ − x0 )e− 4νt dξ
4πνt −∞
1 (x−x0 )2
= √ e− 4νt
4νπt
Then for any arbitrary initial condition f (x), we have
Z ∞
u(x, t) = f (x0 )G(x, x0 , t)dx0
Z−∞

= f (x0 )G(x, ξ, t)dξ
−∞

G(x, ξ, t) is called the Green’s function for the initial value problem defined by (32) and
(33).

## 3 The Laplace Transform

The Fourier Transform cannot handle functions that are not absolute integrable, such as
sin t or a constant. To avoid this difficulty, we can multiply the function by an
exponentially decaying function u(t)e−βt , where

0 t<0
u(t) =
1 t≥0
We can choose β > 0 such that f (t)u(t)e−βt is absolute integrable. We may then perform a
Fourier transform on the modified function
Z ∞
−βt
F{f (t)u(t)e } = f (t)u(t)e−βt e−iωt dt
Z−∞∞
= f (t)e−(β+iω) dt
Z0 ∞
= f (t)e−st (34)
0

9
where s = β + iω is a complex variable. Thus, we define the above integral without the
coefficient as the Laplace transform of f (t) for t ≥ 0.
Z ∞
L{f (t)} = F (s) = f (t)e−st dt (35)
0

## Theorem: If f (t) satisfies

1) piecewise continuous over any interval in [0, +∞]
2) |f (t)| ≤ M eat for sufficient, large t, where M and a are constants,
then the Laplace transform of f (t) exists for Real(s) > a:
Z ∞
F (s) = L{f (t)} ≡ F (t)e−st dt (36)
0

## and its inverse can be calculated as

Z a+i∞
1
f (t) = F (s)e+st ds (37)
2πi a−i∞

The above result follows directly from the Fourier transform theorem. In addition we can
prove that F (s) = L{f (t)} is analytic in the complex domain Real(s) ≥ a1 > a.

Examples:
1) step function 
0 t≤0
f (t) = u(t) =
1 t>0
Direct integration yields Z +∞
1
L{u(t)} = u(t)e−st dt =
0 s
Thus, we have the following Laplace transform pair.
1 1
L{u(t)} = , L−1 { } = u(t)
s s
Other common Laplace transform pairs can also be easily obtain by direct integration as
follows. 2) f (t) = tn

n!
L{tn } =
sn+1
n!
L−1 { } = tn .
sn+1
3) sin ωt
ω
L{sin ωt} =
s2 + ω2
ω
L−1 { } = sin ωt
s2 + ω2

10
4) cos ωt
s
L{cos ωt} =
s2 + ω2
s
L−1 { } = cos ωt
s2 + ω 2
5) e−at
1
L{e−at } =
s+a
1
L−1 { } = e−at
s+a
6)

0 t 6= 0
δ(t) = (38)
∞ t=0

L{δ(t)} = 1
L−1 {1} = δ(t)

## 4 Properties of the Laplace Transform

1. Linearity
For any constants α and β, we have

## L{αf1 (t) + βf2 (t)} = αL{f1 (t)} + βL{f2 (t)}

2. Differentiation
0
L{f (t)} = sF (s) − f (0− )
0
L{f (k) (t)} = sk F (s) − sk−1 f (0− ) − sk−2 f (0− )

3. Integration
Z t
F (s)
L{ f (t)dt} =
s
Z t0
F (s) 1 0
Z
L{ f (t)dt} = + f (t)dt
−∞ s s −∞

4. Translation
A) Let L{f (t)} = F (t) then

L{e−at f (t)} = F (s + a)

11
B) 
0 x<a
f (t − a)u(t − a) =
f (t − a) t ≥ a
L{f (t − a)} = e−as F (s)
Examples:
ω
L{e−at sin ωt} =
(s + a)2 + ω 2
s+a
L{e−at cos ωt} =
(s + a)2 + ω 2
n!
L{e−at tn } =
(s + a)n+1
5. Final value theorem:
Z +∞
0
lim{ f (t)e−st dt} = lim{sF (s) − f (0)}
s→0 0 s→0

Z +∞
0
f (t)dt = lim sF (s) − f (0)
0 s→0

## f (+∞) − f (0) == lim sF (s) − f (0)

s→+∞

Thus,
f (+∞) = lim sF (s)
s→0

The above is true only when the poles of F (s) are all on the left of the imaginery
axis. Simple pole at origin is allowed. No poles on the imaginery axis are allowed.

## f (0+ ) = lim sF (s)

s→∞

7. Convolution
Define the convolution of f (t) and g(t) as
Z t Z t
f (t) ∗ g(t) ≡ f (τ )g(t − τ )dτ = g(τ )f (t − τ )dτ
0 0

Then, we have
L{f (t) ∗ g(t)} = F (s)G(s)

12
5 Laplace Inverse Transform

## According to the Fourier inverse transform of Eqn. (34) we have

Z ∞
−βt 1
f (t)e = F (s)eiωt dω
2π −∞

## for t > 0. Let s = β + iω, we may then write

Z ∞
1
f (t) = F (β + iω)e(β+iω)t dω
2π −∞
Z β+i∞
1
f (t) = F (s)est ds (39)
2πi β−i∞

The above is the Laplace inverse transform formula, it is an integral in the complex
domain. Usually, we can use Residue theorem to find it. For example
 √ 
1 sinh(x s)
W (x, s) = √
s sin h( s)

## eωt − e−ωt eiωt − e−iωt

sinh(ωt) = , sinh(iωt) = = i sin ωt
2 2
eωt + e−ωt eiωt + e−iωt
cosh(ωt) = , cosh(iωt) = = cos ωt
2 2

I
−1 1 X
W (x, t) = L {W (x, s)} = τ W (x, s)est ds = Res{W (x, s)est }
2πi N =1

## W (x, s) has simple poles at sn . In that case we can show

 
Res{W (x, s)e } = lim (s − sn )W (x, s) esn t
st
s→sn

Each singularity in W (x, s) gives rise to an esn t term (exponential growth or decay, or
sinusoidal oscillation, depending on the real part of sn .)

13
Table 1: Some Useful Fourier Transforms
R +∞ 1
R +∞ −iωx
f (x) = −∞ F (ω)eiωx dω F (ω) = 2π −∞ f (x)e dx
f n (x) (iω)n F (ω)
f (x ± a) R∞ e±iaω F (ω)
f (x) ∗ g(x) = −∞ f (x̄)g(x − x̄)dx̄ 2πF (ω)G(ω)
2 2 2 2
e−a x √1 e−ω /4a
a 4π
e−a|x| 1 a
π a2 +ω 2
1
sin ω0 x 2 i[δ(ω + ω0 ) − δ(ω − ω0 )]
1
cos ω0 x 2 [δ(ω + ω0 ) + δ(ω − ω0 )]
1
H(x) 2πiω

## f (t) = L−1 {F (s)} F (s) = L{f (t)}

1
1 s
n!
tn n = 0, 1, 2, · · · sn+1
1
eat s−a s > a
a
sin at s2 +a2 s > 0
s
cos at s2 +a2 s > 0
e−as
H(t − a) s s>0
−as
H(t − a)f (t − a) e F (s)
eat f (t) F (s − a)
Rt
f (t) ∗ g(t) = 0 f (τ )g(t − τ )dτ F (s)G(s)
f n (t) sn F (s) − sn−1 f (0) − · · · − f n−1 (0)
Rt 1
0 f (τ )dτ s F (s)
1 a2 s2
erf (t/2a) s e √erf c(as)
a 1 −a s
erf c( 2√ t
) se
−a2 √
√1 e 4t
πt
e−a/s / s
−1/2 −a2 /4t
p π −a√s
t e √s
e a≥0

−3/2 −a2 /4t 2 π −a s
t e a e a>0

14